Guidance to 2018 good practice: ARIA digitally-enabled, integrated, person-centred care for rhinitis and asthma - Bousquet, Jean (2020)
Aims: Mobile Airways Sentinel NetworK (MASK) belongs to the Fondation Partenariale MACVIA-LR of Montpellier, France and aims to provide an active and healthy life to rhinitis sufferers and to those with asthma multimorbidity across the life cycle, whatever their gender or socio-economic status, in order to reduce health and social inequities incurred by the disease and to improve the digital transformation of health and care. The ultimate goal is to change the management strategy in chronic diseases. Methods: MASK implements ICT technologies for individualized and predictive medicine to develop novel care pathways by a multi-disciplinary group centred around the patients. Stakeholders: Include patients, health care professionals (pharmacists and physicians), authorities, patient’s associations, private and public sectors. Results: MASK is deployed in 23 countries and 17 languages. 26,000 users have registered.